KEPASTIAN HUKUM HAK EKSLUSIF PEMEGANG DESAIN INDUSTRI ATAS TERDAFTARNYA DESAIN INDUSTRI LAIN YANG MENGALAMI PERSAMAAN PENDAFTARAN - MUHAMMAD FIKHRI MIHARDY (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Saidin, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Dr. Jelly Leviza, SH, MHum Industrial design is one of Intellectual Property Rights with aesthetics protected by the Law No. 31/2000 on Industrial Design. However, the Law only protects the registered industrial designs at the Directorate General of Intellectual Property Rights. In accordance with Article 2 paragraph (1) of the Law on Industrial Design which states that the right over an industrial design is only granted to a new one. The designer will receive an Exclusive Right if he registers it. This right is only owned by someone who has an Exclusive Right and other people are prohibited to make, use, sell, import and distribute the product that has been granted a right over the Industrial Design. The research problems are how the efforts of the legal protection for intellectual property rights can be obtained by a designer of an industrial design, how about the registration and annulment of an industrial design in Indonesia which puts priority to novelty principle based on the Law on Industrial Design, and how about the legal protection for the exclusive rights of the owner of the Industrial Design who finds similarities between his design and another design which has already been registered regarding the ruling No: 07/HKI.Desain.Industri/2015/PN-Niaga.Sby. Although the industrial design has been registered, it still has similarities with other designs that cause financial loss to other parties. In fact, the Directorate General of Intellectual Property Rights directly receives the registration of an industrial design if the formal requirements are met. If there is not any refusal from other parties at the time the announcement, the certificate for the industrial design can be issued.A substantive or further inspection is required, but the substantive inspective is conducted only when there is a party files an objection or lawsuit to the court.Keywords: Industrial Design Registration, Exclusive Rights, Novelty